2019
DOI: 10.2224/sbp.7555
|View full text |Cite
|
Sign up to set email alerts
|

The depression status of empty nesters in eastern rural China

Abstract: We used the Geriatric Depression Scale to investigate the depression status of empty nesters living in eastern rural China (N = 967). The results showed that more than half of the participants suffered relatively severe depression and that their mental health was not favorable. Gender, age, level of education, and marital status had a significant influence on depression status. The degree of depression of men was lower than that of women. As participants’ age increased, the degree of depression first rose unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The other nine studies which did not contain non-empty nest samples mainly examined depression, cognitive functions and overall mental health outcomes among older empty nesters. Depression among older empty nesters was frequently assessed with the Geriatric Depression Scale (Su et al , 2012; Xu et al , 2017; Zhou et al , 2019). Other instruments such as the Self-rating Depression Scale, the Center for Epidemiological Studies Depression Scale were also adopted to measure depression (Huang et al , 2019; Lu et al , 2019; Zhang et al , 2019b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The other nine studies which did not contain non-empty nest samples mainly examined depression, cognitive functions and overall mental health outcomes among older empty nesters. Depression among older empty nesters was frequently assessed with the Geriatric Depression Scale (Su et al , 2012; Xu et al , 2017; Zhou et al , 2019). Other instruments such as the Self-rating Depression Scale, the Center for Epidemiological Studies Depression Scale were also adopted to measure depression (Huang et al , 2019; Lu et al , 2019; Zhang et al , 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…Gender was found to be a significant risk factor in older empty nesters’ mental health. Most studies that assessed gender differences within the older empty nester group reported that females had higher prevalence of mental health problems including depression and anxiety disorders than males (Guo et al , 2016; Kaur et al , 2016; Wang et al , 2013; Xu et al , 2017; Zhang et al , 2019b; Zhou et al , 2019). Only one study reported that males had higher prevalence of depression than females (Zhai et al , 2015).…”
Section: Contributors To Older Empty Nesters’ Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations